Developing framework of successful women entrepreneurs in United Arab Emirates (UAE) - Sale, Alsaadi Khalid Yousef Abdulrahman (Tanjong Malim, 2021)
Developing framework of successful women entrepreneurs in United Arab Emirates (UAE) by Sale, Alsaadi Khalid Yousef Abdulrahman